VARIASI PENAMBAHAN PATI SAGU TERMODIFIKASI HMT (HEAT MOISTURE TREATMENT) TERHADAP SIFAT SENSORI MI SAGU INSTAN - Hutagalung, Eva Astriani; Johan, Vonny Setiaries; ', Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objectiveof this research were to produce instant noodles made from nature sago starch and sago starch modified by heat moisture treatment and to get the best sensory properties that meets the indonesian instant noodle standard (SNI 01- 3551- 2000). The design used in this study were completely randomized design with 5 treatments and 4 replications. The treatment were the ratio between nature sago starch and sago starch modified by heat moisture treatment. The data obtained were statistically analyzed using analysis of variance (ANOVA) and followed by a test using Duncan's New Multiple Range Test (DNMRT) at the level of 5%. The results showed, that variation ofnature starch sago and sago starch modified by heat moisture treatment significanly affected organoleptic test except taste, that meets the indonesian instant noodle standard (SNI 01- 3551- 2000). The best sensory propertis are in treatment according to descriptive test of ratio nature sago starch and sago starch modified by heat moisture treatment 1:1 is less colored brown to slightly brown, not flavored sago, slightly chewy texture, whille the hedonic test assessed according to the likes of panelist. Key words: instant noodles, nature sago starch, sago starch modified by heat moisture treatment.